Rydlówka jako pozytywne miejsce pamięci .......... 161 - Zdebska-Schmidt, Joanna; Radecka, Ewelina („Szalony, kto nie chce wyżej, jeżeli może”: Studia i materiały do badań nad życiem i twórczością Heleny Modrzejewskiej, 2025)
RYDLÓWKA AS A POSITIVE SITE OF MEMORYReferring to the concept of a site of memory by Pierre Nora, the text presents the functioning and activities of Rydlówka – a branch of the Museum of Krakow. It shows Rydlówka in both historical and contemporary context, as an important place for the local and supralocal community, referring to positive memory. By presenting the activities and the most important elements of the educational program, the authors try to show how history, memory and identity intertwine in Rydlówka.